2011
DOI: 10.3354/dao02298
|View full text |Cite
|
Sign up to set email alerts
|

Viral load of various tissues of rainbow trout challenged with viral haemorrhagic septicaemia virus at various stages of disease

Abstract: Market-sized rainbow trout Oncorhynchus mykiss were challenged by waterborne exposure to viral haemorrhagic septicaemia virus (VHSV isolate of genogroup Ia). Fish were sampled at 4 stages of infection (before onset of clinical signs, clinically affected fish, mortalities and survivors) and the viral load determined in (1) internal organs, (2) muscle tissue and (3) brain and gill tissue. Virus levels were determined by virus titration and real-time RT-PCR. VHSV was detected by either method in the majority of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 23 publications
1
18
1
1
Order By: Relevance
“…The ability of VHSV to infect the gills has also been correlated to virulence [47]. A study testing the viral load of VHSV in various tissues of rainbow trout at various stages during the course of infection showed that fish surviving a VHSV infection had the highest amount of virus in gill and brain tissue [48].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of VHSV to infect the gills has also been correlated to virulence [47]. A study testing the viral load of VHSV in various tissues of rainbow trout at various stages during the course of infection showed that fish surviving a VHSV infection had the highest amount of virus in gill and brain tissue [48].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a screening survey of VHSV in wild marine fish along the Norwegian coastal line also reported that some wild haddock and whiting were tested positive for VHSV in gills only (Sandlund et al, ). Several studies reported that the tissue tropism transitioned from an acute systemic phase to a chronic phase over the course of a VHS outbreak, and viral persistence is associated with CNS tissue during a chronic phase of infection while virus was mostly cleared from the other tissues (Lovy et al, ; Oidtmann et al, ). Here, VHSV signal was only obtained from gill but not brain and other tissues; thus, we speculated that these VHSV‐positive largemouth bass might be asymptomatic carriers of the virus in an early acute systemic phase, not in a chronic phase.…”
Section: Discussionmentioning
confidence: 99%
“…No data are provided for brain or gills. In a recent study (Oidtmann et al., accepted for publication), we report mean TCID 50 and copy numbers per g of tissue in muscle or gill/brain tissue determined by real‐time RT‐PCR from market‐size rainbow trout between 10 7.0 and 10 9.1 before onset of clinical signs and between 10 4.3 and 10 7.9 in clinically healthy fish still alive after 6 weeks after challenge with VHSV. These viral loads demonstrate that even fish without clinical signs of disease may carry substantial amounts of virus and are expected to have led to transmission under the conditions applied in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Market‐size rainbow trout were exposed to VHSV at concentrations of 5.7 × 10 5 TCID 50 and 5 × 10 4 TCID 50 ml −1 respectively for 4 h while water flow through the tanks was suspended. Rearing conditions were as described in Oidtmann et al. (accepted for publication).…”
Section: Methodsmentioning
confidence: 99%